2011
DOI: 10.12659/msm.881850
|View full text |Cite
|
Sign up to set email alerts
|

Variation in KCNQ1 is associated with therapeutic response to sulphonylureas

Abstract: SummaryBackgroundWe aimed to analyse quantitative effects of treatment with sulphonylurea in addition to metformin on parameters of glycemic control in relation to KCNQ1 genotypes, and to identify factors predictive for the response to sulphonylurea treatment.Material/MethodsEffect of 6-month sulphonylurea therapy in addition to metformin on glycemic control according to KCNQ1 genotypes was evaluated in 87 patients with type 2 diabetes who failed to achieve glycemic control on metformin monotherapy. KCNQ1 rs16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…38 Human carriers of TIID alleles show reduced levels of ms 2 t 6 A 37 , they fail to generate and to secrete insulin, and they may respond differently to pharmacological treatment of TIID. [40][41][42][43][44] Consistent with this, CDKAL1 alleles correlate strongly with an increased risk for coronary artery diseases, most likely as a downstream effect of TIID. 45 Furthermore, CDKAL1 was identified as a risk factor for Crohn's disease (CD) and for Psoriasis.…”
Section: 38mentioning
confidence: 55%
“…38 Human carriers of TIID alleles show reduced levels of ms 2 t 6 A 37 , they fail to generate and to secrete insulin, and they may respond differently to pharmacological treatment of TIID. [40][41][42][43][44] Consistent with this, CDKAL1 alleles correlate strongly with an increased risk for coronary artery diseases, most likely as a downstream effect of TIID. 45 Furthermore, CDKAL1 was identified as a risk factor for Crohn's disease (CD) and for Psoriasis.…”
Section: 38mentioning
confidence: 55%
“…To the best of our knowledge, only two studies have reported the association of KCNQ1 polymorphisms with response to SUs and their results were inconclusive. In a White population, a study including 87 patients with T2DM treated with SUs in addition to metformin for 6 months found a significant genotype-specific effect of rs163184 on the reduction in FPG, with a significantly lower reduction in patients with the GG genotype (P =0.016) [27]. Because the association between rs163184 and T2DM has rarely been reported in the Chinese Han population [34], we did not include rs163184 in our study for the moment.…”
Section: Discussionmentioning
confidence: 99%
“…have evaluated the association of KCNQ1 polymorphisms with SUs response and their results are conflicting [16,27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, to the best of our knowledge, two studies have assessed the KCNQ1 gene and the therapeutic response to SU treatment. The first study evaluated KCNQ1 (rs163184) and the therapeutic response (FPG, HbA1c) to sulfonylurea treatment [38] . However, the patients who were not newly diagnosed with T2DM in this study were not treated with SU monotherapy, and other parameters related to insulin sensitivity and β-cell function were not assessed.…”
Section: Wwwchinapharcom LI Q Et Almentioning
confidence: 99%